Supporting Indicators for the Successful Solid Waste Management Based on Community at Rawajati, South Jakarta - Muhammad Furqan (Jurnal Wilayah dan Lingkungan, 2013)
Community-based waste management is one of the strategies that can be used to overcome the problems of garbage that exist today. However, community-based waste management system could not be implemented as a whole in Indonesia and sometimes some areas are trying to do community-based waste management do not work well and is not sustainable. The purpose of this study was to determine the indicators of success in supporting community-based waste management in Urban Rawajati RW III, South Jakarta. The method of analysis used in this study using quantitative descriptive analysis, and discriminant analysis are useful for describing indicators supporting the success and sustainability of community-based waste management in RW III. Supporting indicators of success in community-based waste RW III, Sub Rawajati divided into 2 main indicators and supporting indicators. The main indicator of success is the use of RW III inorganic waste, the amount of participation, ownership and use of grinding machine home composter are classified into two major variables, namely the participation of society and shape the technology, while the supporting indicators are classified into three variables, namely institutional agreements, operational management and management financially.